A Socio-Semiotic Analysis of the Symbolic Aspects of American Sculptures - Mahmoud, Noor; Al Tameemi, Ibtihal (Al-Adab Journal, 2026)
Sculptures as physical objects are constructed from various materials to commemorate or remember a significant person or an event that plays a crucial role in the historical and cultural heritage of a particular community. The current study delves into the semiotic aspects of American sculptures, focusing on statues and monuments. Whereas previous studies have examined public sculptures from a historical and aesthetic perspective, based on various theoretical frameworks, without conducting a comprehensive analysis of their symbolic elements. This study tries to bridge this gap by providing a more holistic understanding of the sculptures’ symbols. The present study aims to investigate and interpret the symbolic aspects embedded within images of four American sculptures, collected from various websites, from a social semiotic perspective. It also aims to identify the main functions of these symbolic elements in representing the principles of American society. Accordingly, the social-semiotic approach is employed to analyse the selected images, represented by Kress and Van Leeuwen’s (2021) model, in terms of representational, interpersonal, and compositional meta-functions, utilising both qualitative and quantitative methodologies.This investigation reveals that American sculptures communicate meaning systematically, whereas there is a preference for using compositional over the other meta-functions, indicating that the viewer is more interested in how the components are arranged within an image. Moreover, these sculptures represent various functions and serve as a means of communication that encompasses semiotic elements; each represents a particular symbolism, and collectively conveying a specific meaning. The researcher concluded that the symbolic aspects of American sculptures portray the ideals and values of their respective society through historical, cultural, social, and political functions. Additionally, embedding various semiotic elements within sculptures effectively contributes to the visual communication and reinforcement of meanings within a specific culture.